Evaluation of exposure factors to support development of generic recreational reuse scenarios for land reclamation activities. Issue 4 (19th May 2017) - Qian, Hua; Warren, Christopher; Zaleski, Rosemary
ABSTRACT: Recreational reuse of contaminated lands can be a sustainable and cost-effective approach to address the increasing demand on land availability for community development as well as for ecologically valuable conservation areas. Conservatively, residential exposure defaults are often applied for evaluation of an alternative future land use. A risk-based fit-for-purpose approach is preferred in evaluating contaminated sites for reuse purposes. The consideration of exposure factors relevant to the anticipated land use is an important step in performing these assessments. Data from two time activity databases, the Consolidated Human Activity Database (CHAD) and the American Time Use Survey (ATUS), were analyzed for activities that might occur at recreational sites for two important exposure factors: duration and frequency of site activities. The information in these databases indicated that the majority of "doers" spent a total time less than 4–6 h per day on these activities. Only a very small percentage of the survey populations participated in these recreational activities. Limited information on activity frequency was reported in the two data sets. This analysis supports modification to the duration of activities at recreational reuse sites as compared to residential defaults, and provides a basis for the development of alternate values.